Improve plant operations ny [sic] daily monitoring of theoretically derived metrics - Bonem, Joe M. (Knovel, 2012)
"Industrial plants (chemical plants, refineries, compressor stations, et. al.) tend to operate smoothly at design production rates as long as no problems are present. However, in the real world, problem are often present. So improving plant operations almost always involves problem solving. The speed of solving problems determines whether an operating plant meets production, operating costs and quality targets."--Knovel description.
Knovel brief article.
"Apr 17, 2012."
At head of title: Cases.
Keywords: Plant performance -- Monitoring.; Chemical plants.; Petroleum refineries.; elektronické knihy; electronic books